A review of mineral scaling and its mechanisms in Hveragerði geothermal district heating system - Almar Barja 1988- (2014)
Precipitation from geothermal fluid cause serious problems during operation. Clogging of wells, surface equipment and corrosion of pipes are examples of problems arising during production. Many of the problems can be averted or reduced if sufficient research and experience exists beforehand on the reservoir and chemical composition of the geothermal fluid. During production, temperature of the fluid decreases and it boils, leading to super saturation and precipitation of certain minerals. The most common minerals, such as calcite and amorphous silica are well known and extensive research exists on solubility and precipitation rates. Other minerals are often a product of interaction between mixing of geothermal fluid with groundwater and corrosion of surface equipment. Hveragerði district system was established in the 1950s and has since than experienced many different operational problems due to the high dissolved content of the geothermal fluid available. Recently a new scaling mineral was observed in a heat exchanger in Hveragerði. The scale was analyzed by geochemists at Ísor and their findings published in a report for the municipality of Hveragerði. Their findings revealed that the majority of the scaling was made of the iron-carbonate, siderite. Chemical analysis was done on the fluid from the well in 1980 which showed no iron present in the fluid. The iron was assumed to be present due to corrosion within the pipes leading from the well and precipitating in the heat exchanger as ironcarbonate. This paper reviews the results presented in the report and analyses the possibility of sulfide scaling within the pipes due to a reaction between H2S present in the fluid and the dissolved iron. The reason for the precipitation of siderite is also examined since siderite has a retrograde solubility and should not precipitate due to decreasing temperature.